Exploring Post-Colonial Traumatic Experience and Alienation in Tsitsi Dangarembga’s This Mournable Body (2018) - Allali ,Amira; Nouioua ?Wafa (University of Ammar Theledji -Laghouat, 2021)
Postcolonial narratives depict the severe conditions in the period of colonialism and decolonization, placing much emphasis on the physical and psychological sufferance of colonized nations. In this vein, Tsitsi Dangarembga’s latest novel This Mournable Body (2018) portrays the mental distress of her characters in post-colonial Zimbabwe. It is noticeable that the victims of This Mournable Body cannot fully perceive the psychological dilemmas. Thus, this dissertation examines the traumatic experience and alienation of Dangarengba’s characters through a psychoanalytical perspective. Likewise, it explores the disturbing status in neo-liberal Rhodesia, and the causes that led to the characters’ breakdown. In particular, it also aims at exploring racial, classist, and gendered violence and its effects on the psyche of the characters. Moreover, it clarifies the author's intention in writing this narrative with affection and its link with the body's emotions. In order to achieve this aim, the qualitative approach is relevant to this work, and the analytical descriptive method will be used to depict and construe mainly the psychological collapse. Thereupon, this study demonstrates the characters' journey toward success and their attempts to exceed colonialization psychological effects. The characters remain focused on their goals and finally succeed in achieving them by rebelling against discrimination and the patriarchal society